Trade, traders and the ancient city - Parkins, Helen, 1966-; Smith, Christopher John, 1965- (Routledge, 1998)
Trade, exchange and commerce touched the lives of everyone in antiquity, especially those who lived in urban areas. Trade, Traders and the Ancient City addresses the nature of exchange and commerce and the effects it had in cities throughout the ancient world, from the Bronze Age Near East to late Roman northern Italy. Trade, Traders and the Ancient City employs the most recent archaeological, papyrological, epigraphic and literary evidence to present an innovative and timely analysis of the importance and influence of trade in the ancient world.